PENGARUH AKTIVITAS SAMPING TERHADAP TINGKAT PELAYANAN JALAN KEMAKMURAN KABUPATEN PANGKEP - Maryam H; Lambang Basri Said; Mahmud (UNDERPASS Journal of Civil Engineering, Applied Sciences, and Technology, 2022)
Side barriers are one of the causes of traffic jams that can affect the level of service performance of a road. Side resistance is expressed as the interaction between traffic flow and roadside activities related to land use along Jalan Prosperity of Pangkep City which has a significant influence on the size of the effective capacity of the road, and vice versa. The aims of this research are as follows: 1). To study land use and road networks against the characteristics of the Prosperity road section. 2). To analyze the factors of side barriers to the level of service for the Prosperity road in Pangkep City. The development of Pangkep city land use starts from the core development as the center of city activity, develops towards other supporting functions and spreads to fill lands that have not been used intensively. Land use on this road section varies for uses such as housing, gas stations, trading activities and the development of informal sector activities (food stalls). The road network for modes of transportation that are or pass on Jalan Prosperity is very diverse, such as trishaws, motorbikes, trucks, public transport cars and private vehicles. As a result, there is a mix-up that causes a delay, especially in the rickshaw mode. Whereas side friction contributes significantly to road performance in the Prosperity Road study area with an average of 17.28%. Thus, the side barriers on the Prosperity road contribute to a decrease in the level of service on the Prosperity Road as a result of the surrounding land use activities. Prosperity Road functions as a Primary Arterial Road, this is no longer in accordance with its designation so that at this time Prosperity Road can no longer be called a Primary Arterial Road.